Truck Literature from the Drivers’ Perceptions: A Syntactic Analysis - Baruwal, Hira Bahadur (Myagdi Guru, 2022)
This study has explored truck literature: the texts commonly found on buses, trucks, jeeps, motorcycle and taxis. The research has also explored the phenomena behind the use of truck literature: the love of the nation, upward mobility, faith over God, parental influence, life and death, success and failure, union and separation, tears and laughter, ups and downs all connected to their life world. Likewise, this research focuses on the narrative analysis of the texts found on Nepali vehicles. The data derived from the interviews with the drivers and their family members, and observation of the events happened on the parking lots, roads, and market places in the cities of Beni, Baglung, Kusma and Jomsom. Poetic verses, serenades, sayaries and muktaks were collected from the walls of the vehicles. There were eight participants in this study. Mainly, there were two types of data: interview and narratives of the drivers and their family members, and the texts commonly printed on the walls of the vehicles. In this study, fifty-eight texts derived from the field were analyzed. While analyzing data; the thematic approach of data categorization were followed by drawing themes from the data. The texts collected from the field were multilingual in nature as Nepali, Hindi and English. As such, they were multicolored, catchy fonts, and mixed up the words from different languages using the linguistic means of transliteration, code-switching and symbolic adjustments. This analysis offered a profound understanding of the drivers’ experiences and perception within Nepalese society.